2021
DOI: 10.1111/ane.13451
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 vaccines are not free of neurological side effects

Abstract: With interest, we read the article by Lu et al. about a systematic review of published neurological adverse reactions to SARS-CoV-2 vaccines. 1 Included were 48 articles, and it was concluded that no severe neurological adverse reactions to any of the currently available SARS-CoV-2 vaccines have been reported. 1 The review is appealing but raises the following comments and concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 6 publications
0
26
0
1
Order By: Relevance
“…Whether the number of patients with SARS-CoV-2 associated GBS has been declined since the introduction of SARS-CoV-2 vaccines is unknown. Nevertheless, SARS-CoV-2 vaccines are not free from side effects and may not only cause mild or moderate adverse reactions but even severe complications, including neurological side effects (2). Though generally rare, these neurological side effects are increasingly recognized and reported, including SARS-CoV-2 vaccination associated GBS (SCoVaG).…”
Section: ' Introductionmentioning
confidence: 99%
“…Whether the number of patients with SARS-CoV-2 associated GBS has been declined since the introduction of SARS-CoV-2 vaccines is unknown. Nevertheless, SARS-CoV-2 vaccines are not free from side effects and may not only cause mild or moderate adverse reactions but even severe complications, including neurological side effects (2). Though generally rare, these neurological side effects are increasingly recognized and reported, including SARS-CoV-2 vaccination associated GBS (SCoVaG).…”
Section: ' Introductionmentioning
confidence: 99%
“…Vaccines have also been reported as a potential cause of transverse myelitis [19,20]. Other case reports involving transverse myelitis due to administration of COVID-19 vaccines exhibit almost similar symptoms and results [21][22][23][24][25]. Malhotra et al reported their first case of transverse myelitis as an adverse event following the administration of AstraZeneca/Oxford (viral-vectored, recombinant ChAdOX1) COVID-19 vaccine [24].…”
Section: Discussionmentioning
confidence: 97%
“…There have been reports of neurological adverse events following vaccination, such as cerebral venous sinus thrombosis and demyelinating episodes [ 21 ]. Only isolated cases of neurological events were reported in the clinical trials of major SARS-CoV-2 vaccines [ 22 ]. Finsterer et al reported several cases with neurological problems, and it seemed possible that the neurological problems were caused by a recent SARS-CoV-2 vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…An ischemic cerebellar stroke occurred four days after the first dose of a vector-based SARS-CoV-2 vaccination in a 29-year-old woman. A relapsed GBS experienced in a 32-year-old man eight days after receiving the first dose of a vector-based SARS-CoV-2 vaccination [ 22 ]. At least 19 patients with SARS-CoV-2 vaccination associated GBS have been reported as per the end of June 2021 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation